Aplikasi Terminal Sidik Jari Dalam Pemantauan Imunisasi Balita - Sugiyanto, Sugiyanto (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Monitoring  the  implementation  of  immunization  as  an  effort  to  achieve  a  targeted  immunization  Universal  Child  Immunization  ieimmunization  coverage  of  at  least  80%  complete  on  the  baby  evenly  from  all  over  the  village  /  villages  in  Indonesia.  Constraintsrecapitulation  of  data  validation  and  reporting  system  is  running  slow  due  to  the  location  of  posyandu  and  vulnerable  human  errorcommitted by  the officer.  The need for  appropriate  tools  to  support the  monitoring of  immunization  activities,  by combining  hardwareand  software  in the  form of a  fingerprint  terminal  application.  This study uses a  model of  sequential  liner  system design,  software  useBorland  Delphi  7.0,  firebird  database,  as well as components  massanger  yahoo  as  an additional component  in  Borland  Delphi  7.0 forsynchronization  of  text  data  transmission  between  client  computers  and  server  computers.  Hardware  used,  fingerprint,  personal computers,  netbooks  and  GSM  modem.  The  results  of  this  study,  resulting  in  the  application  of  biometric  terminal  for  monitoringimmunization of infants aged 0 to 11 months, with the performance needs of the time synchronization of data, depending on the speed is relatively fast internet bandwidth used.Keywords : Immunization, Fingerprint